2007
DOI: 10.1016/j.cardiores.2006.11.017
|View full text |Cite
|
Sign up to set email alerts
|

The role of angiotensin receptor-1 blockade on electromechanical changes induced by left ventricular hypertrophy and its regression

Abstract: The electromechanical changes to hypertrophied myocardium are different in these two models of LVH. Moreover, losartan was ineffective in modulating the consequences of hypertrophy induced by constriction of the thoracic aorta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…[21][22][23] The study from Yang et al 23 showed a significant reduction of 13% in LVM at day 1 after debanding and subsequent further reduction in LVM, but only in male mice. They identified a typical gene expression profile that was responsible for the fast regression.…”
Section: S26mentioning
confidence: 98%
“…[21][22][23] The study from Yang et al 23 showed a significant reduction of 13% in LVM at day 1 after debanding and subsequent further reduction in LVM, but only in male mice. They identified a typical gene expression profile that was responsible for the fast regression.…”
Section: S26mentioning
confidence: 98%
“…We therefore used techniques to measure directly CV and R j in a set of complimentary studies to test the hypothesis that in intact myocardium CV is a function of R j over a continuous range of values commensurate with moderate, naturally occurring ranges of coupling and uncoupling in pathological conditions. We used validated methods, 5,14 to measure R j and CV and their general relationship in guinea-pig myocardium from different cardiac chambers with and without a GJ blocker, carbenoxolone, and in human ventricular myocardium excised from patients with hypertrophic cardiomyopathy. We also examined the effects of carbenoxolone on local, submillimeter propagation in intact human myocardial propagation as inferred from changes in bipolar electrogram duration during clinical electrophysiology studies to determine how the ex vivo findings are manifest in, and may therefore be inferred from, clinical measurements.…”
Section: Clinical Perspective On P 1214mentioning
confidence: 99%
“…Methods have been described previously in detail 14 ; preparations were superfused with Tyrode solution (37°C, 4 mL·min −1 ) in a horizontal trough. Longitudinal CV was measured by stimulating the preparation at 1 end with insulated Ag-AgCl electrodes (10 µs pulses, 1 Hz, 1.5× threshold).…”
Section: Intracellular Electrophysiological Measurements and Measuremmentioning
confidence: 99%
“…It has been shown previously when using thin trabeculae, as used for G j measurement, and bipolar stimulation at one end that there is one-dimensional (1-D) AP conduction along the longitudinal axis [18]. Under these specific conditions, AP conduction is described accurately by 1-D cable theory where G j is proportional to the square root on CV [7, 16].…”
Section: Resultsmentioning
confidence: 99%
“…Preparations were electrically stimulated with 50–100 μs pulses via Ag/AgCl bipolar electrodes on one end of the preparation [18]. Stimulating conditions were 1, 2 or 5 Hz in Tyrode’s solution and 1 Hz in low-Na solution.…”
Section: Methodsmentioning
confidence: 99%